2018
DOI: 10.15244/pjoes/85200
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Glutathione S-transferase in Bacteria: A Review

Abstract: Cytosolic glutathione S-transferase in bacteria possesses the biochemical capacity to degrade various classes of organochlorine pollutants in the environment in addition to their primary role of defending the organism from a wide range of endobiotics and xenobiotic substrates. Furthermore, the ability of different classes of cGST to recognize a wide repertoire of substrates due the variability in the substrate binding site of the enzymes makes them well suited for bioremediation purposes. cGSTs act as dehaloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…The currently recognized classes of cytosolic GSTs are: alpha, beta, delta, epsilon, zeta, theta, lambda (Lallement et al, 2014), mu, nu, pi, sigma, tau, phi, and omega (for review, see Oakley, 2011). More recently, others GST classes were described in bacteria: nu, zeta, and eta (for review, see Shehu et al, 2018) and in cyanobacteria: chi (Wiktelius and Stenberg, 2007; Pandey et al, 2015) and rho (Pandey et al, 2017). The mitochondrial GSTs share an evolutionary pattern with the cytosolic GSTs but differ from them by their structure and their subcellular localization (Morel and Aninat, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The currently recognized classes of cytosolic GSTs are: alpha, beta, delta, epsilon, zeta, theta, lambda (Lallement et al, 2014), mu, nu, pi, sigma, tau, phi, and omega (for review, see Oakley, 2011). More recently, others GST classes were described in bacteria: nu, zeta, and eta (for review, see Shehu et al, 2018) and in cyanobacteria: chi (Wiktelius and Stenberg, 2007; Pandey et al, 2015) and rho (Pandey et al, 2017). The mitochondrial GSTs share an evolutionary pattern with the cytosolic GSTs but differ from them by their structure and their subcellular localization (Morel and Aninat, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these characters could classy the cytosolic GST C0HLL7 to beta class, which is present only in bacteria. It was also able to conjugate CDNB and was also purified by GSH-affinity chromatography as stated also by Shehu et al (2019). For GPx, Tosatto et al (2008) reported the presence of four important conservation components of GPx active site including; S, Gln, Trp, and Asn.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, both Query sequences of GST and GPx belonged to thioredoxin superfamily showing 73.3 and 76.6% identity, respectively. Therefore, sequences shared more than 40% similarity, belonged to the same class (Shehu et al, 2019). Furthermore, multiple sequence alignments with the top two protein sequences appeared in the hit list, revealed 20 conserved residues for GST C0HLL7.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations